PENGEMBANGAN DESAIN CIRCULAR DAN SQUARE CRASHBOX DENGAN PENAMBAHAN HONEYCOMB SEBAGAI FILLER PADA MODEL BEBAN FRONTAL DAN OBLIQUE - Bayu Agung Wicaksono; Moch. Agus Choiron; Anindito Purnowidodo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
In the previous study, several researchers had developed circular and square crash box designs to enhance energy absorption. In this study, circular and square honeycomb filled crash box is investigated by varying the honeycomb cell dimension. Honeycomb filled is selected due to lightweight and high strength to weight ratio. The crash box modelling was carried out using the finite element method with a frontal and oblique load model. Honeycomb cell dimensions vary by using five models, which are 0%, 25%, 50%, 75% and 100%. This ratio compares the size of honeycomb pitch cell with the inner diameter of crash box. The inner diameter and the crash box thickness are 40 mm and 2 mm, respectively. The single cell wall and the double wall honeycomb thickness are 0,5 mm and 1 mm, respectively. The load model used is an impactor mass of 600 kg with a speed of 15 m/s. For oblique load model, the angle for the load is 300. In this study, energy absorption, deformation pattern and efficiency of the collision force (CFE) were observed, based on the results of computer simulations. The results show that square model with 25% honeycomb filled ratio (S25) has the highest energy absorption, both on frontal and oblique loading. Otherwise, the circle model with 25% honeycomb filled ratio (C25) has the highest CFE value for frontal loading, and S50 has the highest CFE value for oblique loading. The high CFE value is due to the reaction-displacement curve, which is quite stable. The deformation pattern on S25 model due to frontal load model is a diamond mode with five folds. This pattern shows a higher number fold than other square models. Whereas, on oblique load model, the S25 model generates a greater number of folding due to the number of honeycomb cells.